Design and analysis of a voltage‐mode non‐linear control of a non‐minimum‐phase positive output elementary Luo converter - Chincholkar, Satyajit Hemant (2023)
The positive output elementary Luo (POEL) converter is a fourth‐order DC–DC converter having highly non‐linear dynamic characteristics. In this paper, a new dynamic output voltage feedback controller is proposed to achieve output voltage regulation of the POEL converter. In contrast to the state‐of‐the‐art current‐mode controllers for the high‐order boost converters, the proposed control strategy uses only the output voltage state variable for feedback purposes. This eliminates the need for the inductor current sensor to reduce the cost and complexity of implementation. The controller design is accompanied by a strong theoretical foundation and detailed stability analyses to obtain some insight into the controlled system. The performance of the proposed controller is then compared with a multi‐loop hysteresis‐based sliding‐mode controller (SMC) to achieve the output voltage‐regulation of the same POEL converter. The schemes are compared concerning ease of implementation, in particular, the number of state variables and current sensors required for implementation and the closed‐loop dynamic performance. Experimental results illustrating the features of both controllers in the presence of input reference and load changes are presented.